Mining common pathway deregulation profiles in lung diseases - Arakelyan, A.; Nersisyan, L.; Löffler-Wirth, Henry; Binder, Hans (European Respiratory Journal, 2014)
This study is aimed at investigating lung diseases described by common pathomechanisms based on evaluation of gene expression profiles in molecular pathways. 16 datasets containing 428 samples for 22 health conditions were taken from Gene Expression Omnibus. Self organizing maps (Wirth, H. et al.BMC Bioinformatics 2011;12:306) and cluster analysis with dynamic tree cut were used for gene expression based disease clustering. In-house pathway signal flow algorithm and phylogenetic analysis were applied to find common pathway deregulation patterns in clusters.